Typification of the name Gypsophila gasparrinii (Caryophyllaceae) - Roma-Marzio, Francesco; Bartolucci, Fabrizio (Phytotaxa, 2020)
The present contribution is part of an ongoing work promoted by the Italian Botanical Society and aimed to recognize and typify all the taxa described from Italy and their loci classici, in order to increase their systematic knowledge and to promote further studies (Domina et al. 2012, Peruzzi et al. 2015, 2019, Brundu et al. 2017). One of these taxa is Petrorhagia saxifraga (Linnaeus 1753: 413) Link (1829: 235) subsp. gasparrinii (Gussone 1843: 474) Pignatti ex Greuter & Burdet in Greuter & Raus (1984: 44), based on the name Gypsophila gasparrinii Gussone (1843: 474) (Caryophyllaceae Juss.), that appears still untypified.